Tracing reactive power flow and loss in electric power systems - Mohd Herwan, Sulaiman; Mohd Wazir, Mustafa; Omar, Aliman; Ismail, Daut; Surya Hardi, Amrin; Mohamad Suhaizal, Abu Hassan (Regional Energy Resources Information Center (RERIC), Asian Institute of Technology (AIT), 2011)
Link to publisher's homepage at http://www.ait.ac.th/